2021
DOI: 10.1002/aenm.202003340
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial‐Potential‐Gradient Induced a Significant Enhancement of Photoelectric Conversion: Thiophene Polyelectrolyte (PTE‐BS) and Bipyridine Ruthenium (N3) Cooperative Regulated Biomimetic Nanochannels

Abstract: Inspired by photosynthesis, the ion transport‐based artificial light harvesting system shows unprecedented superiority in photoelectric conversion. However, how to high‐efficiently utilize solar energy, just like photosystem I and photosystem II working together in the thylakoid membrane, remains a great challenge. Here, a facile strategy for patterning two photosensitive molecules is demonstrated, that is, thiophene polyelectrolyte (PTE‐BS) and bipyridine ruthenium (N3), onto the two segments of symmetric/asy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 67 publications
0
14
0
Order By: Relevance
“…In contrast, the PT2/N3(T) nanochannels show sharply upward ICR ratios with light illumination, meaning that bulk heterojunction significantly promotes the ion flux at a negative voltage. In order to quantitatively reveal the enhancement of light-induced ion current, the PICC ratio 16 was determined by the following equation of PICC ratio = [( I light − I dark )/ I dark ] ±1V . As a result (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the PT2/N3(T) nanochannels show sharply upward ICR ratios with light illumination, meaning that bulk heterojunction significantly promotes the ion flux at a negative voltage. In order to quantitatively reveal the enhancement of light-induced ion current, the PICC ratio 16 was determined by the following equation of PICC ratio = [( I light − I dark )/ I dark ] ±1V . As a result (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research demonstrated an enhanced photoelectric conversion based on N3/PTE-BS asymmetrical modified nanochannels. 16 However, the separation of light-induced electron–hole pairs (excitons) is suppressed to a certain extent due to the limited diffusion length of excitons, 17 by which the electrons cannot be efficiently transferred and a weak light-induced nanofluid current is observed.…”
Section: Introductionmentioning
confidence: 99%
“…To promote integration of PSI and PSII, attempts have been made to ‘wire’ them to the surface of the electrode. In living photosynthetic organisms, water oxidation catalyzed by PSII generates electrons for the reductive processes driven by PSI, providing the inspiration for a coassembly of PSII and PSI, which achieves in vitro reconstruction of the electron transfer chain of the chloroplast [ 76 ]. Integrating PSII and PSI is challenging because PSII does not directly connect with PSI in nature.…”
Section: Molecular Assembly Of Psii-based Semi-natural Biosystemsmentioning
confidence: 99%
“…Biological ion channels are a critical component of cell or subcellular membranes in the regulation of ion transport for diverse biological processes. , The biological ion channels are naturally asymmetric in structure and surface charge distribution, which is highly associated with the selectivity of ion transport. Ion current rectification (ICR) is a fundamental ion-transport phenomenon in asymmetric ion channels that presents ion enrichment or depletion under an opposite bias voltage. The ICR phenomenon was first discovered in quartz nanopipettes and then received widespread research coverage in biological ion channels, organic or inorganic nanopore/nanochannel, heterogeneous membrane and solid-state electrolytes . Significant progress in understanding the ICR effect brought a wide application of asymmetric nanopore/nanochannel in ionic circuits, ion permeability-selectivity, DNA sequencing, biosensors, and water-energy nexus. …”
Section: Introductionmentioning
confidence: 99%